From Syringes to Dishes: Improving Food Security through Vaccination - Erkmen Giray Aslim; Wei Fu; Erdal Tekin; Shijun You (Institute of Labor Economics (IZA), 2023)
This paper examines the impact of COVID-19 vaccination on food insecurity in the United States, using data from the Household Pulse Survey. Our primary research design exploits variation in vaccine eligibility across states over time as an instrumental variable to address the endogeneity of vaccination decision. We find that vaccination had a substantial impact on food hardship by reducing the likelihood of food insecurity by 24%, with even stronger effects among minority and financially disadvantaged populations. Our results are robust to alternative specifications and the use of regression discontinuity as an alternative identification strategy. We also show that vaccine eligibility had a positive spillover impact on food assistance programs, specifically by reducing participation in the Supplemental Nutrition Assistance Program (SNAP), which suggests that vaccination policy can be effective in alleviating the fiscal burden of the pandemic on the government. Furthermore, our analysis indicates that vaccinated individuals exhibit increased financial optimism, as measured by expectations about future loss of employment and income as well as ability to make mortgage and debt payments. Based on the point estimates, the implied elasticity of food insecurity with respect to financial optimism is between -0.57 and -0.86. Our findings suggest that the COVID-19 vaccination program has implications that extend beyond the direct health benefits. Taken together, our results underscore the critical role of medical innovations and health interventions in improving economic optimism and food security, especially among vulnerable populations, during public health crises.
Keywords: I14; I18; 330; food insecurity; food stamps; vaccination; financial optimism; COVID-19